2018
DOI: 10.1080/13561820.2018.1426559
|View full text |Cite
|
Sign up to set email alerts
|

Development of an interprofessional competency framework for collaborative practice in Japan

Abstract: Rapid aging of the population necessitates improved collaboration among healthcare professionals. Unfortunately, interprofessional collaboration has yet to be implemented effectively in Japan. Therefore, we aimed to develop an interprofessional competency framework for Japanese healthcare professionals. The project was conducted as a four-step process, starting with initial categorization of potential competency domains,, followed by guiding principle and prototype development, feedback on the prototype, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…[30] In addition, GPs are required to cocreate organization dynamics in order to capture multidimensional properties at multiple levels and adapt to internal and external changes, which is also the case when patient well-being is promoted. [31] Moreover, the last two types of approach showed that GPs themselves acted as a learning organization, identi ed team functions which are linked to an interprofessional competency framework, [32] and made dynamic changes which appear to arise in a bottom-up manner rather than as a hierarchical structure. [33] GPs might therefore enhance morale by showing community values through stimulation of re ection by healthcare professionals and staff, and also play a leading role in organizational direction.…”
Section: Discussionmentioning
confidence: 99%
“…[30] In addition, GPs are required to cocreate organization dynamics in order to capture multidimensional properties at multiple levels and adapt to internal and external changes, which is also the case when patient well-being is promoted. [31] Moreover, the last two types of approach showed that GPs themselves acted as a learning organization, identi ed team functions which are linked to an interprofessional competency framework, [32] and made dynamic changes which appear to arise in a bottom-up manner rather than as a hierarchical structure. [33] GPs might therefore enhance morale by showing community values through stimulation of re ection by healthcare professionals and staff, and also play a leading role in organizational direction.…”
Section: Discussionmentioning
confidence: 99%
“…That is, their behavioural modification arose by rational discourse 17 with the physical therapist about the uncertain meanings that the caregivers had begun to recognise and by the physical therapist's approval of their attempts. Of note, interprofessional competency in Japan 26 was developed based on the behavioural characteristics of professionals who achieved high performance in IPC. It consists of six domains, namely two core domains of 'Patient-/Client-/ Family-/Community-Centred' and 'Interprofessional Communication' and four peripheral domains of 'Role Contribution', 'Facilitation of Relationships', 'Reflection' and 'Understanding for Others' (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Now, on approaching the professional skills developed with IPE, we approach the perception of students and its measurement with valid instruments; thus, from this qualitative approach diverse authors gathered from the students that the knowledge and skills they developed most were related with the capacity for reflexion, communication, identification of their role and that of the other, construction of team relationships, collaboration, and mediation to make decisions, to provide patient-centered quality care. (16,17) Other studies have described that when students from the health sciences learn and work in interprofessional teams, they obtain greater clarity of their role and ability to plan tasks than when they are in intra-professional teams, added to the positive impact this has on the sensitization on the role of other professions. (18,19) Moreover, the interventions conducted based on didactics around IPE evidenced promotion in the development of skills related with communication, teamwork, conflict resolution, decision making, roles and attitudes on care by the interprofessional team.…”
Section: Contributions Foundmentioning
confidence: 99%
“…Of the articles analyzed in this thematic, six are in a level of significance of which three are in level 2 (22,23,25) because they are studies of mixed methodology and the rest in level 3 (16,17,26) because they are qualitative studies. With respect to the level of effectiveness, eight articles are presented, of which four correspond to level 2C (15,18,21,28) because of their quasi-experimental designs; one article in level 3E (24) due to being a study without control group and three articles with level 4B (19,20,27) because of being investigations with cross-sectional design.…”
Section: Levels Of Evidencementioning
confidence: 99%